{Constraints on absolute S velocities beneath the Aegean Sea from surface wave analysis} - Bourova, E.; Kassaras, I.; Pedersen, H. A.; Yanovskaya, T.; Hatzfeld, D.; Kiratzi, A. (Geophysical Journal International, 2005)
{The 3-D structure of the lithosphere beneath the Aegean Sea is investigated through surface wave dispersion analysis. Rayleigh and Love waves recorded by 12 broad-band stations installed for a duration of 6 months in the Aegean region are processed through array analysis and Wiener filtering. Data from three GEOFON stations in the area of Crete were also used. The resulting two-station phase velocities are used to determine lateral variations of Rayleigh wave phase velocities between periods of 20 and 100 s by a 2-D ray tomography method. The obtained phase velocities are inverted to calculate variation of S-wave velocity with depth using a combination of linearized inversion and a Monte Carlo based non-linear inversion.The absolute S-wave velocity is resolved to a depth of approximately 200 km. A high-velocity anomaly of 3 per cent is observed in the southern Aegean attributed to the Hellenic subduction. In the northern part of the Aegean, in the prolongation of the North Anatolian Fault which is influenced by strong extensional movements, we found low absolute S-wave velocities at 50–100 km depth. This supports a model of a distributed deformation of the upper mantle in the area. Separate Rayleigh and Love wave phase velocity inversions along common profiles reveal a strong Love–Rayleigh discrepancy in the northern Aegean down to at least 150 km depth, i.e. most probably including the top of the asthenosphere.}